Новые виды галлиц (Diptera, Cecidomyiidae), развивающиеся на гаммаде в Туркменистане - Федотова, З.А. (Вестник зоологии, 1993)
Siefaniola hammadae sp. n. and S. kugitangica sp. n. are described from stem galls. Ualodiplosis hammadae — from coneform bud galls of Hammada leptoclada. Type material is deposited in Zoological Institute, Russian Academy of Sciences (St.-Petersburg), a part of paratypes — in Institute of Zoology, Kazakh Academy of Sciences (Alma-Ata).